School chess and possible articulations with the Specialized Educational Assistance (SEA) of visually impaired students in the municipal network of Novo Hamburgo - Guaríze, Cléber Gomes; Viegas, André Luís (Revista Liberato, 2019)
Specialized Educational Assistance (SEA) is guaranteed by law, however, it is known how difficult and challenging it may be to meet all the demands that inclusive education requires. This article aims to identify the benefits that chess can bring to those who play the game, to report the experience of chess players with visual impairment and their relationship with this playful activity, as well as to discuss the possibility of integrating chess in the care of students with visual impairment in the municipal school network of Novo Hamburgo. For this, firstly, this research presents how the Public Department of Education (SMED), in Novo Hamburgo, State of Rio Grande do Sul, Brazil, uses chess with its students and how the SEA works in the municipality. Secondly, introduces, through references, some of the benefits chess can bring to those who practice it. Thirdly, reports the narratives of three visually impaired chess players and possible articulations with the SEA. Finally, suggests chess as a pedagogical tool.